THE EFFECT OF SMART APPS CREATOR (SAC) LEARNING MEDIA ON THE IMPROVEMENT OF FAHMUL MAQRU' IN CLASS X STUDENTS OF MA DARUT TAQWA PURWOSARI PASURUAN - Ilmiah, Muhibbatul; Hasyim, Mochamad; Rizal, Hasan Syaiful (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2025)
Understanding Arabic reading texts (fahmul maqru') is not just reading, but requires mastery of vocabulary and the ability to understand the content of the text carefully. This phenomenon is a challenge for students of class X of MA Darut Taqwa, coupled with the monotonous method of lectures and the use of package books. Therefore, this study aims to determine the influence of Smart Apps Creator (SAC) interactive learning media on increasing students' fahmul maqru'. This study uses an experimental method with a one group pretest-posttest design. The results of the normality test showed that the data was distributed normally. The N-gain Score of 0.7321 is in the high category and the N-gain percentage of 73.21% is quite effective. The t-test showed a significant increase from pretest (60.50) to posttest (88.83), with a difference of 28.33 points. Thus, SAC media has a significant and quite effective effect on increasing students' fahmul maqru'.